2010
DOI: 10.2528/pierc10092104
|View full text |Cite
|
Sign up to set email alerts
|

BST-Coc Composite Based Rectangular Dielectric Resonator Antenna (Dra) for 2.4 Wlan Wrist Applications

Abstract: Abstract-A rectangular dielectric resonator antenna (DRA) based on Barium Strontium Titanate-Cyclic Olefin Copolymer (BST-COC) composite for 2.4 GHz wrist application is designed and characterized. The dielectric properties of the composite with ∼ 57 vol.% BST loading are characterized using microstrip ring resonator structures at 2.45 GHz frequency. The proposed DRA, fixed onto a reverse grounded FR4 laminate, has a very compact size of 19 mm × 10 mm × 5 mm. The impact of the user's body proximity on the radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Off-center ring DRA has been designed and also used for evaluation of SAR distribution in human head [9]. The performance of rectangular DRA (RDRA) in close proximity with the user's body was studied with the help of a user's hand model [10].…”
Section: Introductionmentioning
confidence: 99%
“…Off-center ring DRA has been designed and also used for evaluation of SAR distribution in human head [9]. The performance of rectangular DRA (RDRA) in close proximity with the user's body was studied with the help of a user's hand model [10].…”
Section: Introductionmentioning
confidence: 99%
“…This shows that, by employing DRA composites, up to 26% enhancement in the impedance bandwidth of the DRA can be achieved. In [17], another DRA composite was presented in which the maximum impedance bandwidth achieved was only 5.92%. However, the modern day wireless communication system demands the antenna to operate in a wider range (N50% impedance bandwidth) of frequencies so that maximum frequency spectrum can be covered with a single antenna.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 96%
“… and , respectively. Mahender et al have then reported an inverted U‐shaped DR‐antenna covering 5.10 GHz‐to‐5.97 GHz for WLAN, followed by a stacked triangular DRA for enhanced bandwidth covering 4.0 GHz‐to‐6.02 GHz with 6.36‐to‐7.98 dBi gain for WLAN applications by Kumari et al A Barium Strontium Titanate‐COC composite rectangular DR‐antenna with 2 dB gain for 2.4 GHz WLAN wrist application has been proposed by Palukuru et al…”
Section: Technology Based Applicationsmentioning
confidence: 99%
“…123 and 124 , respectively. Mahender et al 125 have then reported an inverted U-shaped DR-antenna covering 5.10 GHz-to-5.97 GHz for WLAN, followed by a stacked triangular DRA for enhanced bandwidth covering 4.0 GHzto-6.02 GHz with 6.36-to-7.98 dBi gain for WLAN applications by Kumari et al 126 A Barium Strontium Titanate-COC composite rectangular DR-antenna with 2 dB gain for 2.4 GHz WLAN wrist application has been proposed by Palukuru et al 127 After this, Wang et al 128 have developed a dual-feed dual-polarized mechanism in a DRA for 5.2 GHz WLAN applications with F/B ratio of 10 and 18 dB for port-1 and port-2, respectively. A triple-band DRA with three segments thin dielectric resonating at 2.4, 3.5, and 5.8 GHz for WLAN and WiMAX applications has been reported by Bemani et al 129 An M-shaped conformal patch fed DRA has been modeled by Parmar et al 120 for WLAN 5.15 GHz-to-5.3 GHz and high-performance radio LAN followed by a compact size isosceles trapezoidal shaped DRA with 7.22 dBi gain broadband radiation pattern for 2.4 GHz WLAN applications by Gopakumar and Mathew.…”
Section: Wlanmentioning
confidence: 99%